Development of a Web-Based Supportive Care Program for Patients With Head and Neck Cancer - Fang, Carolyn Y.; Galloway, Thomas J.; Egleston, Brian L.; Bauman, Jessica R.; Ebersole, Barbara; Chwistek, Marcin; Bühler, Janice G.; Longacre, Margaret L.; Ridge, John A.; Manne, Sharon L.; Manning, Cheri (Frontiers in Oncology, 2020)
Patients undergoing radiation treatment for head and neck cancer experience significant side-effects that can impact a wide range of daily activities. Patients often report receiving insufficient information during and after treatment, which could impede rehabilitation efforts; they may also encounter practical and logistical barriers to receipt of supportive care. Thus, we developed a web-based program, My Journey Ahead, to provide information and strategies for managing symptom-focused concerns, which may be easily accessed from the patient’s home. The purpose of this study was to evaluate patient acceptability and satisfaction with the My Journey Ahead program. In Phase 1, five patients with head and neck squamous cell carcinoma (HNSCC) reviewed the web-based program and provided initial feedback, which informed program modifications. In Phase 2, 55 patients were recruited to evaluate the program. Patient assessments were obtained prior to and after use of the web-based program, and included measures of psychological distress, self-efficacy in coping with cancer-related issues, and satisfaction with the website. Among the 55 patients enrolled, 44 logged in and viewed the web-based program. Participants reported high levels of satisfaction with the information received, and indicated that the website was interesting and easy to use. Older age and higher levels of self-efficacy in coping were each associated with higher levels of satisfaction with the website. In summary, the web-based program was well-received by patients, the majority of whom found it to be informative and useful. An easy-to-use web-based program, particularly for older patients who may have difficulty locating reliable evidence-based information on the internet, may be helpful in addressing survivors’ needs in symptom management and coping with cancer. Clinical Trial Registration https://clinicaltrials.gov/, NCT02442336